Antimicrobial activity of Spondias mombin L. aqueous and hydroethanolic extracts on Enterococcus faecalis and Pseudomonas aeruginosa - an in vitro study (Research, Society and Development, 2021)
Objective: To chemically characterize Spondias mombin L. extracts and to evaluate the in vitro antimicrobial activity of these extracts on Enterococcus faecalis and Pseudomonas aeruginosa. Material and methods: Both extracts were submitted to phytochemical prospecting and thin layer chromatography (TLC) analysis prior to determination of Minimum Inhibitory Concentration (MIC), Minimum Inhibitory Adhesion Concentration (MIAC) and Bactericidal Kinetics (BK). The Student’s t-test was used to compare MIC results at the 5% significance level. The chemical characterization, MIAC and BK data were analyzed descriptively. Results: Phenolic compounds, flavonoids, tannins and saponins were detected in the extracts. The hydroethanolic extracts in different concentrations showed statistically superior inhibitory bacterial growth activity (p